The Role of the Teacher in Turning the Character of Students During Pandemic Environments in Sumbang District School Environment - Slamet Pamuji (MANAZHIM, 2022)
The formulation of this problem is: How to bring the character to life during the Covid-19 pandemic. The purpose of this study is: To find out and describe how to bring characters to life during the Covid-19 pandemict. This approach is an approach that focuses on research that is oriented to obtaining findings that cannot be obtained through a quantitative approach. Data collection in this study used several data collection techniques, including; Observation is one of the data collection techniques that is carried out through systematic observations of phenomena in the field. Since the government announced the first case of the 2019 corona virus disease (covid 19) in March 2020 ago, Indonesia has been faced with a pandemic. Almost all sectors of life are affected, including the education sector. Even though this is the case, the school continues to implement and improve the roles of teachers in animate characters, some of the roles of teachers are: teachers as teachers as well as evaluators, teachers as controllers in learning, teachers make learning with various good methods, and teachers be a guide in learning.